Methods of obtaining, verifying, and reusing optimal biological solutions. Issue 1 (1st January 2017) - Yang, Bibo; Yan, Weiwei
Abstract: The practice of using analogies to biological systems for deriving innovative solutions to difficult engineering problems is called biologically inspired design. Although some procedures and methodologies for biologically inspired design have been presented in the literature, they did not specifically support obtaining and applying optimal solutions in living organisms. This article fills this research gap by presenting two methods of obtaining, verifying, and reusing biological optimal solutions (refer to biological forms, shapes, and structures) to solve engineering optimisation problems. The first method develops an analytical model, formulates an optimisation problem explicitly, and then verifies the optimal solution theoretically. An application example of this method is provided. The second method is based on experiments, and uses experimental design and statistical analysis to verify the optimal solution. This method is applied to the design of the flapping Micro Air Vehicles, which reuse an optimal biological solution (the shape of dragonfly wing). The procedures, requirements and advantages of both methods are discussed. We show that by using the two methods, scientists and engineers can efficiently obtain, verify, and reuse the optimal solutions from biological organisms.